Sensory Perception of Non‐Deuterated and Deuterated Organic Compounds - Salthammer, Tunga; Monegel, Friederike; Schulz, Nicole; Uhde, Erik; Grimme, Stefan; Seibert, Jakob; Hohm, Uwe; Palm, Wolf‐Ulrich (Chemistry : a European journal, 2021)
The chemical background of olfactory perception has been subject of intensive research, but no available model can fully explain the sense of smell. There are also inconsistent results on the role of the isotopology of molecules. In experiments with human subjects it was found that the isotope effect is weak with acetone and D6‐acetone. In contrast, clear differences were observed in the perception of octanoic acid and D15‐octanoic acid. Furthermore, a trained sniffer dog was initially able to distinguish between these isotopologues of octanoic acid. In chromatographic measurements, the respective deuterated molecule showed weaker interaction with a non‐polar liquid phase. Quantum chemical calculations give evidence that deuterated octanoic acid binds more strongly to a model receptor than non‐deuterated. In contrast, the binding of the non‐deuterated molecule is stronger with acetone. The isotope effect is calculated in the framework of statistical mechanics. It results from a complicated interplay between various thermostatistical contributions to the non‐covalent free binding energies and it turns out to be very molecule‐specific. The vibrational terms including non‐classical zero‐point energies play about the same role as rotational/translational contributions and are larger than bond length effects for the differential isotope perception of odor for which general rules cannot be derived. The scent of deuterium: For a mechanistic understanding of the olfactory perception of molecules, it is an interesting aspect whether or not isotopological substances are perceived differently. To investigate this question, humans and a trained sniffer dog were exposed to deuterated and non‐deuterated substances. The experimental results, supplemented by quantum mechanical calculations, provide insights into the interaction of molecules with receptors.